KEPEMIMPINAN KEPALA SEKOLAH DALAM PERUMUSAN TUJUAN KELEMBAGAAN - Asmuni; Sirozi, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Leadership in educational institutions plays a strategic role in formulating institutional goals aligned with the vision, mission, and values of the institution. This study examines the role of leadership in directing, guiding, coordinating, and optimizing resources to achieve educational objectives efficiently and effectively. Using a qualitative approach based on content analysis, the focus includes the management of human and financial resources, strengthening organizational culture, the utilization of technology and innovation, and strategic planning. Additionally, the importance of effective communication, performance evaluation, and adaptive leadership are identified as key success factors. The findings show that leadership based on professionalism and innovation can enhance the effectiveness of educational institution management, especially in the context of decentralization and the implementation of school-based management. This conclusion offers guidance for educational leaders to face challenges and improve the quality of education management sustainably.